Joint disruption of Ret and Ednrb transcription shifts cell fate trajectories in the enteric nervous system in Hirschsprung disease - Ryan D. Fine; Rebecca Chubaryov; Mingzhou Fu; Gabriel Grullon; Aravinda Chakravarti (Proceedings of the National Academy of Sciences, 2025)
Despite extensive genetic heterogeneity, 72% of pathogenic alleles for Hirschsprung disease (HSCR) arise from coding and regulatory variants in genes of the RET and EDNRB gene regulatory network (GRN) in the enteric nervous system (ENS). To elucidate the mechanisms leading to enteric neuronal loss from these genetic defects, we generated four strains of mice carrying reduced function alleles at Ret or Ednrb or both, along with their wild-type alleles. ENS tissue- and single-cell gene expression profiling of the developing and postnatal gastrointestinal tract in these five mouse models revealed three major insights: i) Ret and Ednrb deficiency, rather than complete loss, is sufficient to induce HSCR, ii) Ret and Ednrb demonstrate strong trans interactions, and iii) disruption of this interaction leads to cellular fate changes to compensate for neuronal loss. Critically, we show the combined reduction of signaling of these two receptors below a threshold in enteric neural crest-derived cells (ENCDCs) leads to a molecular tipping point at which otherwise lesser cellular defects result in aganglionosis. This study of targeted mouse models of a multifactorial disorder reveals how increasing dosage of genetic defects within a GRN leads to quantifiably increasing dysregulation from genotype to gene expression to cellular identity to function. Importantly, our studies establish that aganglionosis results only with severely reduced gene expression at both receptor genes and their consequent disruption of normal and compensatory cell fate trajectories.